Genetic Variations in AMPK, FOXO3A, and POMC Increase the Risk of Extreme Obesity - Cinthia Vila Nova Santana; Luiz Alexandre Viana Magno; Adauto Versiani Ramos; Maria Angélica Rios; Valéria Cristina Sandrim; Luiz Armando De Marco; Débora Marques de Miranda; Marco Aurélio Romano-Silva (Journal of Obesity)
Conclusions: These findings indicate that factors beyond traditional metabolic pathways, potentially related to feeding behavior or hormonal regulation, may also link these genetic variations to obesity. Further research in a larger sample is essential to validate these findings and explore their potential to guide clinical interventions and public health strategies.